Material in silico adaptation and validation of an ovine heart model for blunt cardiac trauma applications - Thomas, Patricia K.; Rutherford, Olivia; Hsu, Fang-Chi; Gayzik, F. Scott (Frontiers in Mechanical Engineering, 2025)
IntroductionBlunt cardiac trauma (BCT) is seen throughout high-velocity blunt thoracic trauma, and while it is considered to be low prevalence, it often leads to fatalities. The finite element ovine thorax model (FE-OTM) was developed to investigate high-velocity blunt trauma and the resulting injuries; however, it has a simplified cardiac geometry that does not consider cardiac muscle nor differences in chamber behavior.Methods This study seeks to improve upon the heart within the FE-OTM v2 through the additions of more anatomically correct mesh geometry with muscle fiber directionality and material constitutive models for each chamber that considers hyperelasticity and anisotropy. Newly added regions with improved material models included the right and left atria, the right and left ventricles, and the septum.Results and DiscussionThe ventricles and septum were made of hexahedral solid elements that included myocardial fiber directions, whereas the atria were made of quadrilateral elements due to the lack of anisotropy in literature. The final cardiac geometry included about 21k nodes, 53k elements, 13 individual parts, and 10 constitutive material models. The heart was then implemented into the existing model and re-validated based on peak forces using a subject-specific simulation matrix. A paired t-test was conducted to quantitatively validate the model, where p = 0.85, signifying that the model and experimental forces were similar. The FE-OTM v3 with the updated heart geometry and materials can be used in future work focusing on BCT risk.